2006
DOI: 10.1073/pnas.0600744103
|View full text |Cite
|
Sign up to set email alerts
|

Recombination between elongation factor 1α genes from distantly related archaeal lineages

Abstract: Homologous recombination (HR) and lateral gene transfer are major processes in genome evolution. The combination of the two processes, HR between genes in different species, has been documented but is thought to be restricted to very similar sequences in relatively closely related organisms. Here we report two cases of interspecific HR in the gene encoding the core translational protein translation elongation factor 1␣ (EF-1␣) between distantly related archaeal groups. Maximum-likelihood sliding window analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…To our knowledge, previously published reconstructions of ancient protein families have not been impacted by known partial HGT events. While it has been shown that partial HGT events have occurred within the EF-1a sequences of some archaeal lineages (Inagaki et al 2006), these groups were not included in the published ancestral reconstruction of homologous bacterial EF-Tu proteins (Gaucher et al 2003).…”
Section: Partial Hgt and Ancestral Reconstructionmentioning
confidence: 99%
“…To our knowledge, previously published reconstructions of ancient protein families have not been impacted by known partial HGT events. While it has been shown that partial HGT events have occurred within the EF-1a sequences of some archaeal lineages (Inagaki et al 2006), these groups were not included in the published ancestral reconstruction of homologous bacterial EF-Tu proteins (Gaucher et al 2003).…”
Section: Partial Hgt and Ancestral Reconstructionmentioning
confidence: 99%
“…Second, the generally low rates of point mutation (8,9) and the relatively high degree of sequence conservation of chloroplast and plant mitochondrial genes increase the probability that these genes might at least occasionally recombine with one another. Third, although the frequency of homologous recombination correlates positively and tightly with DNA sequence similarity and decreases sharply with the level of relatedness between donor and recipient (10,11), several cases have nonetheless been reported in recent years of recombination between sequences that are distantly related in time and/or sequence (5,(12)(13)(14)(15). Finally, 2 cases are now known of plant mitochondrial housekeeping genes that have a clear history of chimerism, through recombination between native mitochondrial genes and foreign copies acquired via horizontal gene transfer from other, distantly related angiosperms (16,17).…”
mentioning
confidence: 99%
“…It has been shown, how-ever, that genetic material integrated via LGT can constitute an entire gene (41,104), a partial (fragmentary) gene (10,49,75), or multiple (entire or fragmentary) adjacent genes, including multigene operons (34,48,81). We recently examined the transfer of genes and gene fragments among 144 prokaryote genomes (15,18), demonstrating that studies focusing entirely on whole-gene transfer are likely to underestimate the extent of LGT.…”
mentioning
confidence: 99%